The Importance of Family Education on The Formation of Social Attitude And Independence of Children In The Industrial Revolution 4.0 - Linda Safitri; Naenul Muna; Rizki Kurnianto (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2019)
Children's social awareness in Indonesia tends to be still low. This can be seen from the emergence of difficulties children develop social attitudes in themselves, such as the attitude of cooperation and  socializing with their environment. In fact, social attitudes and independence are needed in the future. Therefore family education is the most important education to shape social attitudes and independence of children. This study aims to explain the importance of family education towards the formation of social attitudes and children's independence.This study uses the results of studies from journals and books collected and then described and analyzed. The conclusion of this study is that Family Education influences the Formation of Social Attitudes and Children's Independence in the Industrial Revolution Era 4.0.